A nitrogen-boron co-doped modified biochar and its preparation process and application

By introducing nitrogen and boron co-doping and complex pore structures on biochar, the problem of difficulty in removing antibiotic pollution in traditional sewage treatment technology is solved, efficient antibiotic decomposition and conventional organic pollutant removal are achieved, and higher water treatment effect is provided .

CN118847049BActive Publication Date: 2024-12-27SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411349998.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Traditional sewage treatment technology is difficult to completely remove antibiotic pollutants in water, especially sulfamethoxazole (SMX), which cannot achieve its complete decomposition, resulting in potential threats to the environment and human health.

Method used

Modified biochar with nitrogen-boron co-doping, with a micropore structure of 5-30μm and a nanopore of 2-10nm on the surface. The complex pore structure and high specific surface area are introduced through high-temperature pyrolysis of urea and boric acid, combining N and B Doping of high-density surface defects and rich functional groups, enhancing the adsorption and catalytic treatment capabilities of SMX.

Benefits of technology

The decomposition rate of antibiotic pollutants in water has reached more than 85%, which significantly improves the removal efficiency of antibiotics and is suitable for the removal of conventional organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847049B_ABST
    Figure CN118847049B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sewage treatment, and discloses a nitrogen-boron co-doped modified biochar and a preparation process and application thereof. The surface of the nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-30 μm, and the microporous structure is composed of nanopores with a size of 2-10 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 700-730 m 2 / g, ID:IG value is 0.8-0.9. The purpose of the present invention is to solve the problem of difficulty in removing antibiotics from water in the prior art. The nitrogen-boron co-doped modified biochar has a high specific surface area, a complex pore structure, surface defects and more abundant functional groups, which can not only remove conventional organic pollutants in water, but also remove antibiotic pollutants in water, so that the decomposition rate of antibiotic pollutants in water reaches more than 85%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and in particular to a nitrogen-boron co-doped modified biochar and a preparation process and application thereof. Background Art

[0002] The problem of antibiotic pollution has become an urgent environmental and public health challenge. Antibiotic residues, especially sulfamethoxazole (SMX), have become ubiquitous pollutants in the environment due to their wide application and limited bioavailability. The global annual consumption of SMX is huge, but due to its low absorption rate in organisms, a large amount of residues enter the environment through excretion, posing a potential threat to ecosystems and human health. Traditional sewage treatment technologies have limitations in dealing with antibiotic pollution, especially in achieving complete mineralization of pollutants. Although adsorption technology can temporarily reduce the concentration of antibiotics in water bodies, it cannot achieve its complete decomposition, and thus cannot fundamentally solve the problem of antibiotic pollution.

[0003] CN118287040A A nitrogen-boron co-doped waste tea biochar adsorbent and its preparation method and application. First, dihydrogen diamine and boric acid are dissolved in deionized water to form a precursor, and then waste tea particles are added to the mixed solution. The mixed solution is freeze-dried to obtain an adsorbent powder, and then the adsorbent powder is carbonized in an inert atmosphere at high temperature to obtain a nitrogen-boron co-doped waste tea biochar adsorbent material. The material has a simple composition, a high specific surface area and high adsorption performance, and has a significant adsorption effect on chloroquine phosphate and hydroxychloroquine sulfate, but cannot decompose antibiotics.

[0004] CN112108117A A preparation method and testing device for simultaneously removing multiple radioactive metals from a shaped carbon-based composite material. The method uses modified activated carbon, magnesium oxide, zinc oxide, vermiculite, silver nitrate, silicon dioxide, iron oxide and nitrogen-boron co-doped titanium silicon molecular sieve as raw materials to prepare a shaped carbon-based composite material in the form of columnar or spherical particles or honeycomb cubes, and uses a testing device to simultaneously adsorb and fix radioactive isotopes of cerium, cesium, strontium, uranium and heavy metals such as nickel, cobalt, lead, cadmium, mercury and chromium in water pollutants. The results show that the removal rate of the shaped carbon composite material for cerium, cesium, strontium, uranium, nickel, cobalt, lead, cadmium, mercury and chromium within a low concentration of less than 100 ppb is as high as 99%, and the removal rate for high concentrations of 5-10 ppb is as high as 100 ppb. The removal rate of mg / L cerium, cesium, strontium, uranium, nickel, cobalt, lead, cadmium, mercury and chromium is as high as over 90%, and the total adsorption capacity for cerium, cesium, strontium, uranium, nickel, cobalt, lead, cadmium, mercury and chromium ions is as high as 0.8-1g / g.

[0005] In summary, nitrogen-boron co-doping technology is currently used in the field of sewage treatment, but it is still difficult to remove antibiotics from water bodies. Summary of the invention

[0006] To solve the above problems, the present invention provides a nitrogen-boron co-doped modified biochar and its preparation process and application, which can not only remove conventional organic pollutants in water bodies, but also remove antibiotic pollutants in water, so that the decomposition rate of antibiotic pollutants in water reaches more than 85%.

[0007] To achieve the above object, the technical solution of the present invention is:

[0008] A nitrogen-boron co-doped modified biochar, wherein the surface of the nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-30 μm, the microporous structure is composed of nanopores with a size of 2-10 nm, and the specific surface area of ​​the nitrogen-boron co-doped modified biochar is 700-730 m 2 / g, ID:IG value is 0.8-0.9.

[0009] The nitrogen-boron co-doped modified biochar disclosed in the present invention has obvious distinguishing features compared to the original biochar. The surface of the original biochar is relatively smooth, while the nitrogen-boron co-doped modified biochar mentioned in the present invention presents a rough wrinkled structure with a microporous structure of 5-30μm. This solution uses urea and boric acid in the preparation. The high-temperature pyrolysis of these two substances will produce volatile gases, thereby destroying the surface structure of the biochar, and can introduce nanopores with a size of 2-10 nm in the subsequent reaction. At the same time, these nanopores are not simply spread on a plane, but are constructed into the above-mentioned 5-30μm microporous structure, so that the nitrogen-boron co-doped modified biochar has a complex pore structure, and microporous wrinkles are formed on its surface, so that the specific surface area can reach 700m 2 / g or more. At the same time, ID:IG is the defect degree of biochar, and the pyrolysis temperature, the ratio of boric acid, urea and biomass will affect the defect degree of biochar. After design and experiments, the nitrogen-boron co-doped modified biochar prepared by the process of the present invention has an ID:IG value of 0.8-0.9. Combined with technical characterization methods such as SEM, it is found that there is a large amount of amorphous carbon on its surface. The successful doping of N atoms and B atoms in the biochar matrix makes the nitrogen-boron co-doped modified biochar have a high density of surface defects, which ensures the electron transfer ability for the catalytic treatment of antibiotics in water bodies. Therefore, the nitrogen-boron co-doped modified biochar described in this scheme has a high specific surface area, a complex pore structure, more surface defects and richer functional groups, which provides more active sites for the effective adsorption of SMX.

[0010] The present invention further discloses a preparation process of the nitrogen-boron co-doped modified biochar, comprising the following steps:

[0011] Step (1): crushing and sieving the washed biochar source to obtain a sieved material;

[0012] Step (2): taking 90-110 parts of the sieved material, 5-15 parts of boric acid and 5-15 parts of urea, mixing them thoroughly, adding them into 200-240 parts of water, stirring and soaking them, and then drying them to obtain a dry mixed material;

[0013] Step (3): carbonizing the dry mixed material obtained in step (2) under protective gas for 1-3 hours, and obtaining a carbonized material after cooling, wherein the carbonization temperature is 700-900°C;

[0014] Step (4): washing, filtering and drying the carbonized material to obtain nitrogen-boron co-doped modified biochar.

[0015] Preferably, in step (1), the biochar source is one or more of corn stalks, rice straw, wheat stalks and sorghum stalks.

[0016] This scheme is applicable to any grass plant, tree, shrub, etc., which has a high-fiber plant body, that is, the carbon source itself is a plant.

[0017] Preferably, in step (1), the particle size after sieving is 20-100 mesh.

[0018] The plant carbon source has high toughness and is not easy to break. If the particle size is larger than 100 mesh, it is not easy to pass through the sieve. However, the finer the particle size, the more beneficial it is to the subsequent reaction. Therefore, the larger the mesh size, the more likely the carbonization reaction described in step (3) can proceed.

[0019] Preferably, in step (2), the stirring and infiltration time is 1-3 hours; the drying treatment is spray drying, oil bath evaporation or low-temperature drying, and the drying treatment temperature is 80-120°C.

[0020] The stirring and infiltration in step (2) is mainly to disperse the biochar source particles and fully infiltrate the particles in the boric acid and urea solution. Therefore, in the actual operation, any stirring that can disperse, such as magnetic stirring, mechanical stirring, and ultrasonic assisted stirring, can be used under the premise of sufficient infiltration. In order to prevent the carbon element of the biochar source particles from oxidizing during the drying process, the drying process needs to be carried out under low temperature conditions. After drying, the urea and boric acid dissolved in water will be uniformly precipitated on the surface of the biochar source particles, which improves the uniformity of subsequent pore formation and ensures the uniform distribution of N and B elements on the surface of the final product.

[0021] Preferably, in step (3), the protective gas is nitrogen, carbon dioxide or argon.

[0022] The protective gas is also used to prevent the biochar source particles from being oxidized at high temperatures to produce carbon dioxide. This ensures the following reactions:

[0023] ;

[0024] Preferably, in step (3), the carbonization is carried out in a tubular furnace, and the heating rate of the carbonization is 3-8°C / min.

[0025] If the carbonization heating rate is too fast, although nitrogen-boron co-doped modified biochar can be generated, and it also has a nanoporous structure, it cannot form a microporous structure, that is, it cannot present a rough wrinkled structure. In addition, the biochar source particles are dehydrated too quickly, and urea and boric acid are also decomposed at a relatively fast rate. The above reactions (1)-(4) are restricted, and it is impossible to obtain abundant active sites. On the contrary, if the heating rate is too slow or the insulation time is too long, the microporous structure is too large, the nanoporous structure swallows up each other and grows, and the side reactions will increase, which will also affect the performance of the final product.

[0026] Preferably, in step (4), the detergent used to wash the carbonized material is ethanol and ultrapure water. After the carbonized material is naturally cooled, it is washed alternately with ethanol and ultrapure water for multiple times. After thorough washing, a black powder is obtained, i.e., moist nitrogen-boron co-doped modified biochar.

[0027] Preferably, in step (4), the drying condition is 80-120° C. in a vacuum environment.

[0028] The drying conditions are also to prevent oxidation of the nitrogen-boron co-doped modified biochar.

[0029] The present invention also discloses the application of the nitrogen-boron co-doped modified biochar, and the nitrogen-boron co-doped modified biochar is applied to water treatment.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] 1. The nitrogen-boron co-doped modified biochar of the present invention has a high specific surface area, a complex pore structure, more surface defects and richer functional groups. It can not only remove conventional organic pollutants in water bodies, but also remove antibiotic pollutants in water, making the decomposition rate of antibiotic pollutants in water reach more than 85%.

[0032] 2. The raw materials of the present invention are widely available, the preparation process is simple, it can adapt to large-scale production, and it provides a path for the resource utilization of agricultural waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a microscopic morphology of the nitrogen-boron co-doped modified biochar described in Example 1 of the present invention;

[0034] Figure 2 This is a microscopic morphology of conventional biochar described in Comparative Example 1 of the present invention;

[0035] Figure 3 This is a microscopic morphology of the boric acid-modified biochar described in Comparative Example 7 of the present invention;

[0036] Figure 4 This is a microscopic morphology of the urea-modified biochar described in Comparative Example 8 of the present invention;

[0037] Figure 5 This is a morphology of the nanopores of the nitrogen-boron co-doped modified biochar described in Example 1 of the present invention;

[0038] Figure 6 This is the EDS mapping image of Example 1 of the present invention, which represents the distribution state of the four elements C, O, N, and B. DETAILED DESCRIPTION

[0039] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0041] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0042] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0043] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0044] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0045] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-30 μm, and the microporous structure is composed of nanopores with a size of 2-10 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 728 m 2 / g, ID:IG value is 0.85.

[0046] Example 2: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0047] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0048] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0049] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 1 hour, the heating rate of the tubular furnace is 8°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0050] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0051] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-20 μm, and the microporous structure is composed of nanopores with a size of 2-8 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 713 m 2 / g, ID:IG value is 0.90.

[0052] Example 3: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0053] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0054] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0055] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 8°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0056] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0057] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-30 μm, and the microporous structure is composed of nanopores with a size of 2-10 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 720 m 2 / g, ID:IG value is 0.89.

[0058] Example 4: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0059] Step (1): crush the washed rice straw, and sieve it through a 40-mesh sieve to obtain a sieved product;

[0060] Step (2): Take 100 parts of the sieved material, 15 parts of boric acid and 15 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0061] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 8°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0062] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0063] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-25 μm, and the microporous structure is composed of nanopores with a size of 2-9 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 725 m 2 / g, ID:IG value is 0.90.

[0064] Example 5: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0065] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0066] Step (2): Take 100 parts of the sieved material, 5 parts of boric acid and 5 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0067] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0068] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0069] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-15 μm, and the microporous structure is composed of nanopores with a size of 2-8 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 700 m 2 / g, ID:IG value is 0.88.

[0070] Example 6: A nitrogen-boron co-doped modified biochar is prepared by the following process steps:

[0071] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0072] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0073] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 3 hours, the heating rate of the tubular furnace is 3°C / min, the carbonization temperature is 800°C, and the carbonized material is obtained after cooling;

[0074] Step (4): the carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80° C. to obtain nitrogen-boron co-doped modified biochar;

[0075] The surface of the prepared nitrogen-boron co-doped modified biochar has a microporous structure with a size of 10-30 μm, and the microporous structure is composed of nanopores with a size of 5-10 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 712 m 2 / g, ID:IG value is 0.88.

[0076] Comparative Example 1: Conventional biochar, i.e., no boric acid and urea were added during the preparation, and the rest of the process was the same as in Example 1.

[0077] Comparative Example 2: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0078] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0079] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0080] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 3 hours, with a heating rate of 3°C / min and a carbonization temperature of 850°C, and obtaining a carbonized material after cooling;

[0081] Step (4): The carbonized material was cross-washed with clean water and alcohol, filtered, and dried in a vacuum oven at 80°C. The obtained nitrogen-boron co-doped modified biochar surface had a microporous structure of 5-50 μm in size and a specific surface area of ​​550 m 2 / g, ID:IG value is 0.78.

[0082] Comparative Example 3: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0083] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0084] Step (2): Take 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0085] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 0.5 h, with a heating rate of 10°C / min and a carbonization temperature of 650°C, and obtaining a carbonized material after cooling;

[0086] Step (4): The carbonized material was cross-washed with clean water and alcohol, filtered, and dried in a vacuum oven at 80°C. The obtained nitrogen-boron co-doped modified biochar had nanopores with a size of 2-300 nm on the surface and a specific surface area of ​​643 m 2 / g, ID:IG value is 0.86.

[0087] Comparative Example 4: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0088] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0089] Step (2): Take 100 parts of the sieved material, 3 parts of boric acid and 3 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry blend;

[0090] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0091] Step (4): The carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80°C. The obtained nitrogen-boron co-doped modified biochar surface has a microporous structure of 5-30 μm in size, and the microporous structure is composed of nanopores of 2-10 nm in size, with a specific surface area of ​​440 m 2 / g, ID:IG value is 0.85.

[0092] Comparative Example 5: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0093] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0094] Step (2): Take 100 parts of the sieved material, 20 parts of boric acid and 20 parts of urea, mix them thoroughly, add them into 200 parts of water, soak them for 2 hours with magnetic stirring, and then dry them in an oil bath at 110° C. to obtain a dry mix;

[0095] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0096] Step (4): The carbonized material is cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80°C to obtain a nitrogen-boron co-doped modified biochar having a microporous structure of 5-30 μm on the surface, wherein the microporous structure is composed of nanopores of 2-10 nm in size and has a specific surface area of ​​610 m 2 / g, ID:IG value is 0.85.

[0097] Comparative Example 6: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0098] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0099] Step (2): taking 100 parts of the sieved material, 10 parts of boric acid and 10 parts of urea and mixing them thoroughly to obtain a dry mixture;

[0100] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0101] Step (4): The carbonized material was cross-washed with clean water and alcohol, filtered, and dried in a vacuum drying oven at 80°C to obtain a modified biochar with a specific surface area of ​​378 m 2 / g, ID:IG value is 0.85.

[0102] Comparative Example 7: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0103] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0104] Step (2): taking 100 parts of the sieved material and 10 parts of boric acid and mixing them thoroughly to obtain a dry blend;

[0105] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0106] Step (4): The carbonized material was cross-washed with water and alcohol, filtered, and dried in a vacuum drying oven at 80°C to obtain boric acid-modified biochar with a specific surface area of ​​540 m 2 / g, ID:IG value is 0.76.

[0107] Comparative Example 8: A nitrogen-boron co-doped modified biochar prepared by the following process steps:

[0108] Step (1): crushing the washed corn stalks, and sieving them through a 40-mesh sieve to obtain a sieved product;

[0109] Step (2): taking 100 parts of the sieved material and 10 parts of urea and mixing them thoroughly to obtain a dry mixture;

[0110] Step (3): carbonizing the dry mixed material obtained in step (2) in a tubular furnace under nitrogen protection for 2 hours, the heating rate of the tubular furnace is 5°C / min, the carbonization temperature is 700°C, and the carbonized material is obtained after cooling;

[0111] Step (4): The carbonized material was cross-washed with water and alcohol, filtered, and dried in a vacuum drying oven at 80°C to obtain urea-modified biochar with a specific surface area of ​​276 m 2 / g, ID:IG value is 0.73.

[0112] Morphology and performance testing:

[0113] 1. Microscopic morphology and technical characterization: inspection and analysis of relevant inspection technology equipment, such as Figure 1 , Figure 2 As shown;

[0114] 2. Performance test: 40 mg of biochar was dispersed in 200 ml of 25.3 mg / L SMX solution, and then sampled and filtered with a 0.22 μm polyethersulfone (PES) filter at specified time intervals, and the residual concentration of SMX was tested. Isothermal adsorption experiments were conducted at 25°C, 40 mg of biochar was dispersed in 40 mg / L SMX solution, and samples were taken, filtered and the SMX concentration was tested after 60 minutes.

[0115] The performance test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] The nitrogen-boron co-doped modified biochar Examples 1-6 have an absolute advantage in SMX decomposition rate over Comparative Examples 1-8.

[0119] Comparative Examples 1, 7 and 8 are conventional biochar, boric acid modified biochar and urea modified biochar, respectively. Conventional biochar has only adsorption function and poor SMX decomposition ability, which can be regarded as an intrinsic value. The SMX removal rate of boric acid modified biochar and urea modified biochar is improved to a certain extent compared with conventional biochar, but it still cannot meet the demand. The nitrogen-boron co-doped modified biochar of Examples 1-6 has a qualitative improvement in SMX decomposition ability compared with boric acid modified biochar and urea modified biochar. There are two reasons for this:

[0120] 1. The surface of the nitrogen-boron co-doped modified biochar prepared in Example 1 has a microporous structure, such as Figure 1 As shown, the microporous structure of the surface of the nitrogen-boron co-doped modified biochar prepared in Example 1 is Figure 5 The nanopore structure shown in the figure is constructed. Since the micropores and nanopores cannot be of uniform size, they cannot be characterized by a single data point and can only be described by the pore size range. The surface of comparative example 1 is relatively smooth. Figure 2 , Comparative Example 8 has a microporous structure, see Figure 4 , but no nanoporous structure; the surface of comparative example 7 becomes rough, see Figure 3 , but there is no microporous structure, which makes the specific surface area of ​​Example 1 much higher than that of Comparative Example 1, Comparative Example 7 and Comparative Example 8, and the adsorption performance is also stronger. That is, the combined effect of urea and boric acid introduces more micropores (about 2-10 nm, see Figure 5 ) enhances the pore structure of Example 1. The high specific surface area combined with the developed pore structure can significantly improve the adsorption capacity and mass transfer process in the catalytic process.

[0121] 2. EDS spectrum (Figure 6) shows that the labels C, O, N, and B in the figure refer to the corresponding sub-diagrams of the distribution of these four elements in the sample. It can be seen that after modification with boric acid and urea, N and B in Example 1 are uniformly doped in the biochar framework. Boron doping alone mainly greatly improves the adsorption rate of biochar; however, when nitrogen and boron are co-doped into biochar, the adsorption rate and degradation rate are significantly improved. This shows that in the nitrogen-boron co-doped modified biochar prepared under the process conditions of the present invention, the doping of B and N is not just a simple superposition effect, but through a complex synergistic effect, it promotes the adsorption efficiency and the oxidation removal of SMX.

[0122] As shown in Comparative Example 3, the carbonization heating rate is too fast. Although nitrogen-boron co-doped modified biochar can be generated and also has a nanoporous structure, a large number of microporous structures cannot be formed, that is, a complex wrinkled structure cannot be presented. In addition, the biochar source particles are dehydrated too quickly, and urea and boric acid are also decomposed at a relatively fast rate, and abundant active sites cannot be obtained, resulting in a low SMX decomposition rate and poor performance compared with the data in the embodiment.

[0123] On the contrary, if the heating rate is too slow or the holding time is too long, the micropore structure is too large, the nanopore structures swallow each other and grow, and the side reactions will increase, which will also affect the performance. As shown in Comparative Example 2, this phenomenon may also be due to the decomposition of cellulose, hemicellulose and lignin in the biochar caused by the increase in pyrolysis temperature. Further increasing the pyrolysis temperature may cause the pore structure to collapse and the specific surface area to affect its adsorption rate.

[0124] Comparative Examples 4 and 5 represent the cases where too little and excessive amounts of urea and boric acid are added, respectively. When too little is added, the prepared nitrogen-boron co-doped modified biochar has insufficient surface active functional groups and an insufficient number of nanopores, and cannot present a complex wrinkled structure; when too much is added, similar to Comparative Example 2, the nanopore structures grow by absorbing each other, resulting in a decrease in specific surface area.

[0125] In Comparative Example 6, since the biochar source was not soaked in urea and boric acid solution, the urea and boric acid were unevenly distributed, and the contact surface with the biochar source particles was small, and the synergistic effect of urea and boric acid was not reflected, so the structure shown in Example 1 did not appear. The soaking process is not just a surface wetting process. Cellulose has the characteristics of water absorption and swelling. In this process, urea and boric acid can enter between cellulose molecules along with the water absorbed into cellulose, providing a guarantee for the subsequent uniform distribution of B and N elements.

[0126] The above results jointly verify the successful doping of N atoms and B atoms in the biochar matrix; the modified biochar surface shows stronger SSA, pore structure, more surface defects and richer functional groups; these modifications provide more active sites for the effective adsorption and degradation of antibiotic substances such as SMX.

[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A nitrogen-boron co-doped modified biochar, characterized in that: The surface of the nitrogen-boron co-doped modified biochar has a microporous structure with a size of 5-30 μm, and the microporous structure is composed of nanopores with a size of 2-10 nm. The specific surface area of ​​the nitrogen-boron co-doped modified biochar is 700-730 m 2 / g, ID / IG value is 0.8-0.9; The preparation method of the nitrogen-boron co-doped modified biochar comprises the following steps: Step (1): crushing and sieving the washed biochar source to obtain a sieved product; the biochar source is one or more of corn stalks, rice straw, wheat stalks and sorghum stalks; the particle size after sieving is 20-100 mesh; Step (2): taking 90-110 parts of the sieved material, 5-15 parts of boric acid and 5-15 parts of urea, mixing them thoroughly, adding them to 200-240 parts of water, stirring and soaking them, and then drying them to obtain a dry mixed material; the stirring and soaking time is 1-3 hours; the drying treatment is spray drying, oil bath evaporation or low temperature drying, and the drying treatment temperature is 80-120°C; Step (3): carbonizing the dry mixed material obtained in step (2) for 1-3 hours under protective gas, and obtaining a carbonized material after cooling, wherein the carbonization temperature is 700-800° C.; the carbonization is carried out in a tubular furnace, and the heating rate of the carbonization is 3-8° C. / min; Step (4): washing the carbonized material, filtering it, and drying it in a vacuum environment at 80-120° C. to obtain nitrogen-boron co-doped modified biochar.

2. A method for preparing nitrogen-boron co-doped modified biochar as claimed in claim 1, characterized in that: The following steps are involved: Step (1): crushing and sieving the washed biochar source to obtain a sieved product; the biochar source is one or more of corn stalks, rice straw, wheat stalks and sorghum stalks; the particle size after sieving is 20-100 mesh; Step (2): taking 90-110 parts of the sieved material, 5-15 parts of boric acid and 5-15 parts of urea, mixing them thoroughly, adding them into 200-240 parts of water, stirring and soaking them, and then drying them to obtain a dry mixed material; The stirring and soaking time is 1-3h; the drying treatment is spray drying, oil bath evaporation or low temperature drying, and the drying treatment temperature is 80-120°C; Step (3): carbonizing the dry mixed material obtained in step (2) for 1-3 hours under protective gas, and obtaining a carbonized material after cooling, wherein the carbonization temperature is 700-800° C.; the carbonization is carried out in a tubular furnace, and the heating rate of the carbonization is 3-8° C. / min; Step (4): washing the carbonized material, filtering it, and drying it in a vacuum environment at 80-120° C. to obtain nitrogen-boron co-doped modified biochar.

3. The method for preparing nitrogen-boron co-doped modified biochar according to claim 2, characterized in that: In the step (3), the protective gas is nitrogen, carbon dioxide or argon.

4. The method for preparing nitrogen-boron co-doped modified biochar according to claim 2, characterized in that: In the step (4), the detergents used to wash the carbonized material are ethanol and ultrapure water.

5. An application of the nitrogen-boron co-doped modified biochar as claimed in claim 1, characterized in that: The nitrogen-boron co-doped modified biochar is used to remove antibiotic pollutants in water.